Dampak ASEAN China Free Trade Agreement (ACFTA) terhadap Pertumbuhan Ekonomi Indonesia - Aisyah Bunga Chaidir; Wita Hapsari; Aditya Narayan (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This research aims to analyze the impact of Indonesia's participation in the ASEAN-China Free Trade Agreement (ACFTA) on national economic growth, especially in the contribution of exports and imports. Based on data, since the implementation of ACFTA, Indonesia's trade flows with ASEAN countries and China have increased, but imports from China far exceed exports, creating a significant trade deficit. In 2018, Indonesia's trade deficit with China reached 18.41 billion USD. Although international trade offers opportunities for economic growth, this imbalance creates challenges, especially for domestic industrial sectors that must compete with cheaper imported products. Research also shows that every 1% increase in Indonesia's per capita income drives an increase in imports by 1.04%. However, ACFTA also opens up opportunities for Indonesia to increase the added value of export products through global supply chain integration. By supporting the right policies to increase the competitiveness of local industry and reduce dependence on imported products, Indonesia can take advantage of ACFTA to encourage more inclusive economic growth.